TES bolometer arrays for the QUBIC B-Mode CMB experiment - Marnieros, S; Ade, P; Alberro, JG; Azzoni, S (Springer, 2020)
QUBIC is a ground-based experiment aiming to measure the B-mode polarization of the cosmic microwave background. The developed instrument is an innovative two-frequency band bolometric interferometer that will operate at 300 mK with NbSi TES arrays. In this paper, we describe the fabrication process of the detectors.